2005
DOI: 10.1007/s11010-005-3673-0
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of adipogenin, an adipocyte plasma transmembrane protein, during adipogenesis

Abstract: Until now, the various proteins highly expressed in adipose tissues have been identified and characterized by traditional gene cloning techniques.However, methods of computer analysis have been developed that compare levels of expression among various tissues, and genes whose expression levels differ significantly between tissues have been found. Among these genes, we Confocal image analyses of green-fluorescent protein-adipogenin (pEGFP-adipogenin) transiently expressed in 3T3-L1 adipocytes showed that adipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
2
28
1
Order By: Relevance
“…Stem cell isolation procedure was performed as described previously [Gimble and Guilak, 2003a;Hong et al, 2005;Niemela et al, 2007]. Briefly, human adipose tissue specimens were cut into small pieces, enzymatically digested with 0.05% collagenase I (Invitrogen, Paisley, UK) in Dulbecco's Modified Eagle's Medium Nutrient Mixture F-12 (Gibco, Invitrogen, Carlsbad, Calif., USA) for 60 min at 37 ° C in a gyratory water bath.…”
Section: Isolation and Culture Of Hascsmentioning
confidence: 99%
“…Stem cell isolation procedure was performed as described previously [Gimble and Guilak, 2003a;Hong et al, 2005;Niemela et al, 2007]. Briefly, human adipose tissue specimens were cut into small pieces, enzymatically digested with 0.05% collagenase I (Invitrogen, Paisley, UK) in Dulbecco's Modified Eagle's Medium Nutrient Mixture F-12 (Gibco, Invitrogen, Carlsbad, Calif., USA) for 60 min at 37 ° C in a gyratory water bath.…”
Section: Isolation and Culture Of Hascsmentioning
confidence: 99%
“…This was because a report by Hong and coworkers (wherein Smaf1 was named Adipogenin) indicated that knockdown of Smaf1 in preadipocytes, followed by treatment of with adipogenic inducing agents, resulted in adipocytes with reduced lipid content [18]. This study was different from ours in that the siRNA for Smaf1 was delivered to 3T3-L1 preadipocytes first (rather than at the adipocyte stage as carried out herein); Smaf1 is not expressed in preadipocytes.…”
Section: Sirna-mediated Knockdown Of Smaf1 Does Not Alter Key Aspectsmentioning
confidence: 59%
“…Following our report on the identification of Smaf1, this gene was also reported as adipogenin (Adig) by Hong and coworkers. In that study it was identified via public database mining for adipose-enriched transcripts [18]. However their study also did not provide information as to the nature of the endogenous Smaf1 gene product.…”
Section: Introductionmentioning
confidence: 99%
“…The HCV-related lipid deregulation causes overexpression of different hepatic enzymes: hormone sensitive Lipase (LIPE), lipoprotein lipase (LPL) and Leptin [15]. Accordingly, patients exhibit serum lipid abnormalities, such as low levels of: LDL [16,17], Resistin (RETN) [18], Adiponectin (ADIPOQ) [19] and Adipogenin (ADIG) [20]. The genes involved in the lipid de novo synthesis and beta oxidation, such as the nuclear receptor Liver X Receptor alpha (LXR alpha), the Sterol regulatory element binding transcription factor 1 (SREBP1c), the Fatty acid synthase (FASN) and the Acetyl CoA carboxylase Beta (ACACB) respectively, are associated with HCV infection, too [21], as well as Fatty acid binding protein 4 (FABP4) that modulates inflammatory and metabolic response that is mainly expressed in adipocytes and macrophages [22].…”
Section: Introductionmentioning
confidence: 99%